Protective effects of Exocarpium Citri Grandis against sepsis-induced acute lung injury via PANoptosis inhibition - Xu, Zaibin; Wang, Kongyan; Hu, Huiyu; Chen, Yan; Qiu, Yi; Cai, Jiazhong; Li, Weirong; Luo, Zhuohui; Li, Hang; Huang, Jiawen (Frontiers in Nutrition, 2025)
Sepsis-induced acute lung injury (ALI) is a life-threatening condition with high mortality, driven by dysregulated inflammation and programmed cell death. Exocarpium Citri Grandis (ECG), which refers to the dried outer rind of the Rutaceae plant Citrus grandis ‘Tomentosa’ or Citrus grandis (L.) Osbeck, has a history of use in treating pulmonary inflammatory diseases, yet its mechanism of action against sepsis-induced ALI remains unexplored. In this study, we investigated the therapeutic potential of ECG in a murine model of sepsis induced by cecal ligation and puncture (CLP). This study reveals that ECG significantly reduces the levels of IL-1β, IL-6, and TNF-α in both serum, bronchoalveolar lavage fluid (BALF) and in lung tissue. Additionally, ECG downregulates the abnormal expression of chemokine genes. Molecular dynamics simulations revealed that Naringin and Neohesperidin, active compounds of ECG, form stable complexes with the PANoptosis-related proteins ZBP1 and RIPK1. The protective effect of ECG was mediated through the simultaneous targeting of multiple programmed cell death pathways, as it inhibited NLRP3/Caspase-1/GSDMD-driven pyroptosis, suppressed Bcl-2/Bax/Caspase-3-dependent apoptosis, and attenuated ZBP1/MLKL/RIPK1-induced necroptosis. Our study identifies ECG as a multi-target therapeutic agent that mitigates sepsis-induced ALI primarily through the inhibition of PANoptosis, providing a mechanistic foundation for its potential development as a functional food or dietary intervention strategy.